Skill Demand and Wages. Evidence from Linked Vacancy Data - Lennart Ziegler (Institute of Labor Economics (IZA), 2021)
This study provides new evidence on skill requirements in the labor market and shows to what extent skill demand is associated with wages and vacancy duration. Using more than 1.5 million job postings administered by the Austrian public employment service, I identify the most common skill requirements mentioned in job descriptions. Because employers in Austria are legally required to state the minimum remuneration for advertised positions, it is possible to relate the skill content of jobs to wage postings. Moreover, I estimate skill associations with starting wages for a subset of vacancies which can be matched to administrative data on employment spells of eventual hires. Accounting for education, work experience, and firm and occupation fixed-effects, there exists a robust association between the number of skill requirements and wages. In particular, jobs with many skill requirements pay substantially higher wages. While I estimate large effects for managerial and analytical skills, associations with most soft skills are small. Employers also need longer to fill vacancies with many skill requirements. Robustness tests show that measurement error is unlikely to explain these results and that the estimates can be replicated using vacancy postings from another job board.
Keywords: J23; J24; J31; 330; job advertisements; job boards; skills; wage differentials; vacancy duration